THE USE OF ARTIFICIAL INTELLIGENCE IN ADVANCING MEDICAL DIAGNOSIS (CIPEEX, 2025)
Artificial Intelligence (AI) has emerged as a promising tool to enhance medical diagnostics. The use of advanced algorithms allows for faster and more accurate disease identification, optimizing medical care. This study aimed to analyze the bibliographic production on the impact of AI in medical diagnostics. It is na integrative review of scientific production on the impact of AI in medical diagnostics. The research was conducted in the National Library of Medicine (PubMed) and Virtual Health Library (VHL) databases, using the descriptors “patients,” “artificial intelligence,” “conventional diagnostics,” and “precision.” Articles published in the last 5 years, in Portuguese and English, with 3 studies included, were reviewed. The studies indicate that AI improves diagnostic accuracy in various fields and reduces the time required for detecting complex conditions. AI shows great potential to complement clinical judgment, increasing the efficiency and quality of care. It is particularly valuable in oncology, aiding in the early detection of cancers and the personalization of treatments, and also significantly contributes to cardiology, where it is used to predict and monitor heart conditions. It is concluded that artificial intelligence has a significant and positive impact on the field of medical diagnostics. The reviewed studies demonstrate that AI not only improves diagnostic accuracy but also accelerates the detection process, which is crucial for complex and rapidly progressing conditions such as cancer and heart diseases. Additionally, AI can act as a valuable complement to clinical judgment, offering additional support to healthcare professionals, which can lead to more informed and personalized patient treatment decisions.
Keywords: artificial intelligence; medicine; diagnosis